The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1021/acs.estlett.0c00244
|View full text |Cite
|
Sign up to set email alerts
|

Chlorines Are Not Evenly Substituted in Chlorinated Paraffins: A Predicted NMR Pattern Matching Framework for Isomeric Discrimination in Complex Contaminant Mixtures

Abstract: Chlorinated paraffins (CPs) can be mixtures of nearly a half-million possible isomers. Despite the extensive use of CPs, their isomer composition and effects on the environment remain poorly understood. Here, we reveal the isomeric distributions of nine CP mixtures with single-chain lengths (C 14/15 ) and varying degrees of chlorination. The molar distribution of C n H 2 n+ 2 –m Cl … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(44 citation statements)
references
References 62 publications
1
41
0
Order By: Relevance
“…A recent study suggested that the first, second, and third carbons from an end of the chain and central carbons all have differing likelihood of chlorination. 19 Also, it has been known that chlorination occurs less likely to the neighbors of the carbon that is already chlorinated due to a steric effect, 20,21 which is also inferred by GC retention measurements for CP mixtures. 4,22 Nevertheless, in highly chlorinated CP mixtures, dichloro-substituted carbons and trichloromethyl groups have also been identified.…”
Section: Predictions Of Partition Coefficients For Congener Groups Umentioning
confidence: 89%
See 1 more Smart Citation
“…A recent study suggested that the first, second, and third carbons from an end of the chain and central carbons all have differing likelihood of chlorination. 19 Also, it has been known that chlorination occurs less likely to the neighbors of the carbon that is already chlorinated due to a steric effect, 20,21 which is also inferred by GC retention measurements for CP mixtures. 4,22 Nevertheless, in highly chlorinated CP mixtures, dichloro-substituted carbons and trichloromethyl groups have also been identified.…”
Section: Predictions Of Partition Coefficients For Congener Groups Umentioning
confidence: 89%
“…4,22 Nevertheless, in highly chlorinated CP mixtures, dichloro-substituted carbons and trichloromethyl groups have also been identified. 19,23 Since general rules for positions of Cl for CPs of different lengths and chlorination degree are still under investigation, we opted for the fully random and "one Cl per C" rules to generate congener sets for this work.…”
Section: Predictions Of Partition Coefficients For Congener Groups Umentioning
confidence: 99%
“…Third, the current work used randomly generated congeners from all Cl substitution patterns or excluding double and triple Cl substitutions to represent the congener composition of each CP congener group, but this is a first approximation. As more and more knowledge regarding Cl substitution patterns in the bulk CP mixtures is becoming available, 19,23,31 congener compositions used for the prediction of partition coefficients could be elaborated further.…”
Section: Resultsmentioning
confidence: 99%
“…A recent study suggested that the first, second, and third carbons from an end of the chain and central carbons all have differing likelihood of chlorination. 19 Also, it has been known that chlorination occurs less likely to the neighbors of the carbon that is already chlorinated due to a steric effect, 20,21 which is also inferred by GC retention measurements for CP mixtures. 4,22 Nevertheless, in highly chlorinated CP mixtures, dichloro-substituted carbons and trichloromethyl groups have also been identified.…”
Section: Predictions Of Partition Coefficients For Congener Groups Umentioning
confidence: 89%
See 1 more Smart Citation